A hydrogen-bonded antibacterial curdlan-tannic acid hydrogel with an antioxidant and hemostatic function for wound healing. (1st June 2022) - Zhou, Zongbao; Xiao, Jiangwei; Guan, Shuwen; Geng, Zhijie; Zhao, Ruifang; Gao, Botao
Abstract: Manufacturing facile and low-cost wound dressings that simultaneously meet the needs of the entire repair process remains the major challenge of effective wound healing. Herein, a series of curdlan-tannic acid hybrid hydrogels were successfully fabricated through the annealing technique. Notedly, when the mixing weigh ratio was 1:1, the hydrogel exhibited excellent physicochemical properties, including swellability, degradability, water retention, porosity, and rheology. Additionally, the hydrogel did not display significant cytotoxicity to fibroblasts and the hemolysis rate at 12 h was 3%. Interestingly, the hybrid hydrogel showed multifunctional properties, including remarkable antioxidant, antibacterial, and rapid hemostasis effects reduce blood loss by 0.35 g, that were achieved through the temperature-dependent release of tannic acid. Moreover, a full-thickness skin defect animal model was used to verify that the multifunctional hydrogel could accelerate wound healing in vivo . These results suggest that this hybrid hydrogel is a promising candidate for the clinical treatment of full-thickness wounds. Graphical abstract: Unlabelled Image Highlights: A novel curdlan/tannic acid hydrogel was prepared by annealing technology. Curdlan/tannic acid hydrogel performed adjustable physicochemical properties. The developed hydrogel represented high safety features on mammalian cells. The developed hydrogel showed an outstanding effect on wound healing progress.